A MULTIDIMENSIONAL ANALYSIS OF THE ECONOMIC, SOCIAL, AND ENVIRONMENTAL CONSEQUENCES OF THE DEVELOPMENT OF THE SEMARANG-DEMAK TOLL ROAD - Caroline; Sumarjiyanto B. M, Nugroho; Iskak; Ernawa, Aeda; Subekti, Riyuniawan (Universitas Tidar, 2025)
The Semarang-Demak Toll Road was constructed as a strategic component of the Indonesian government's initiatives to enhance regional connectivity and promote economic development in Central Java. Nevertheless, this endeavor not only generates intricate social and environmental consequences, but also generates economic advantages. The objective of this investigation is to identify and evaluate the social, economic, and environmental consequences of the toll road's construction. The study will concentrate on social inequality, population migration, changes in settlement patterns, and environmental degradation, including erosion, inundation, and pollution. The multidimensional approach that simultaneously integrates social, economic, and environmental analysis in the context of large-scale infrastructure development is the unique feature of this study. This approach has not been comprehensively investigated in the case of the Semarang-Demak Toll Road. Quantitative and qualitative methodologies are implemented, which encompass surveys, in-depth interviews, field observations, and secondary data analysis. The research sample was purposively selected from the community, local economic actors, and policy makers along the toll corridor. The study's findings suggest that while toll road construction can enhance economic development and accessibility, it also has negative repercussions, including decreased environmental quality, changes in spatial planning, and social inequality. Therefore, a mitigation strategy is required in the form of sustainable development, community involvement, and inclusive government policies to ensure that economic benefits are equitable and that social and environmental aspects are not sacrificed. This research is a significant contribution to the development of sustainable and equitable infrastructure development policies.